The evolution of Malaysian cartoon animation / Faryna Mohd Khalis...[et al.] - Mohd Khalis, Faryna; Mustaffa, Normah; Shahizan Ali, Mohd Nor; Mohamed Salim, Neesa Ameera (2019)
A cartoon can be defined as an unrealistic style of sketching and or funny figures that can make people laugh. Aside from entertainment purposes, cartoons are also used to send messages without a serious tone and indirectly telling something sarcastically. In April 2019, Malaysia was shocked by the headline that ‘Doraemon’ had been selected to represent the Japanese themed cartoon exhibition in conjunction with Visit Malaysia 2020. Malaysian art activists, specifically those who has a cartoon animation background, were very upset and expressed their dissatisfaction with the news. Local legendary cartoonist Datuk Lat also showed his disappointment and made a stand that a local cartoon character should have been chosen to represent Malaysia. Therefore, this research aims to illustrate the development of Malaysian cartoons from when they first started in newspapers, until their existence today in the form of animation on digital platforms. In sequence, Malaysia produced cartoons in newspapers, magazines, blogs, television and cinema, whereby this is in parallel with the development of technology. From handdrawn art for ‘Usop Sontorian’ to digital animation for the film ‘Upin dan Ipin’, Malaysians should be more appreciative and proud of our local cartoons rather than those from other countries.